Thermodynamic modelling of BFS-PC cements under temperature conditions relevant to the geological disposal of nuclear wastes. (May 2019) - Prentice, Dale P.; Walkley, Brant; Bernal, Susan A.; Bankhead, Mark; Hayes, Martin; Provis, John L.
Abstract: Intermediate level waste produced in UK nuclear power generation is encapsulated or immobilised in blended cements comprising blast furnace slag (BFS) and Portland cement (PC), to be emplaced in a proposed geological disposal facility (GDF). The wasteforms are expected to be exposed to temperatures from 35 to 80 °C during the initial 150 years of GDF operation. Thermodynamic modelling is applied here to describe the phase assemblages of hydrated 1:1, 3:1 and 9:1 BFS-PC blends, with the participation of hydrogarnet as an important phase above 60 °C. The chemical composition of the main phase forming in these systems, an aluminium rich calcium silicate hydrate (C-A-S-H), was well described by a solid-solution model with explicit Al incorporation, although the Al/Si ratio was systematically slightly under-predicted. The developed thermodynamic model predicts the correct phase assemblage across varying temperature regimes, making it a valuable tool to assess the effects of temperature on cements.